2020
DOI: 10.3390/microorganisms8060896
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterisation of a Multiple Drug Resistant IncHI2 ST4 Plasmid in Escherichia coli ST744 in Australia

Abstract: Antibiotic resistance genes (ARGs) including those from the blaCTX-M family and mcr-1 that encode resistance to extended spectrum β–lactams and colistin, respectively, have been linked with IncHI2 plasmids isolated from swine production facilities globally but not in IncHI2 plasmids from Australia. Here we describe the first complete sequence of a multiple drug resistance Australian IncHI2-ST4 plasmid, pTZ41_1P, from a commensal E. coli from a healthy piglet. pTZ41_1P carries genes conferring resistance to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 75 publications
(135 reference statements)
1
17
0
Order By: Relevance
“…However, IncHI2 plasmids, carrying mcr-1 gene, showed higher diversity than other plasmid groups. As previously described in other IncHI2 plasmids (Wyrsch et al, 2015 ; Zingali et al, 2020 ), diversity of these molecules was mainly observed in MDR regions, and could be explained by acquisition and/or loss of transposons, insertion sequences, and antimicrobial resistance genes. In addition, mobile elements play a significant role in the formation of hybrid plasmids and instances where resistance plasmids have fused are known (Mangat et al, 2017 ).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, IncHI2 plasmids, carrying mcr-1 gene, showed higher diversity than other plasmid groups. As previously described in other IncHI2 plasmids (Wyrsch et al, 2015 ; Zingali et al, 2020 ), diversity of these molecules was mainly observed in MDR regions, and could be explained by acquisition and/or loss of transposons, insertion sequences, and antimicrobial resistance genes. In addition, mobile elements play a significant role in the formation of hybrid plasmids and instances where resistance plasmids have fused are known (Mangat et al, 2017 ).…”
Section: Discussionsupporting
confidence: 63%
“…IncHI2 plasmid backbones were composed of regions for replication ( reHI2 ), conjugative transfer ( tra genes), and plasmid maintenance ( par gene). Additionally, IncHI2 plasmids (except pMCR_1139_D1) carried tellurium resistance genes ( terZABCDEF ), commonly associated with this plasmid family, in addition to terY1, terY2 , and terW (Zingali et al, 2020 ). Also, IncHI2 plasmids (except pMCR_915_E1 and pMCR_1085_C1) carried the operons encoding sil and pco , conferring resistance to copper and silver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of NCBI databases using MEGABLAST revealed the 10 plasmids most closely related to pSG17-135-HI2 were not of Australian origin. While MDR IncHI2 plasmids have reportedly been isolated within Australian porcine operations (41)(42)(43)(44), these plasmids vary in their pMLST types and carry different AMR gene cargo in comparison with pSG17-135-HI2. Instead, this analysis revealed that pSG17-135-HI2 is more closely related to IncHI2 plasmids from China and Taiwan from various sources (Table S3), particularly pCFSA1096 (GenBank accession number CP033347).…”
Section: Resultsmentioning
confidence: 99%
“…IncHI2 plasmid backbones were composed of regions for replication ( reHI2 ), conjugative transfer ( trh genes), and plasmid maintenance ( par gene). Additionally, IncHI2 plasmids carried tellurium resistance genes ( terZABCDEF ), commonly associated with this plasmid family, in addition to terY1 , terY2 , and terW ( 20 ). Also, genes conferring arsenic resistance ( arsCBRH ) were found in IncHI2 plasmids.…”
Section: Observationmentioning
confidence: 99%